Impact of Job Satisfaction on Job Performance of Nurses at Al-SuwairaGeneral Hospital - okab, ammar (Iraqi National Journal of Nursing Specialties, 2017)
Objective(s): To measure the level of job satisfaction and job performance of nurses and to find out the association between participants’ socio-demographic characteristic of nurse and their job satisfaction and job performance. Methodology: A descriptive analytic study design was carried out to measure the nurses’ level of job satisfaction and job performance in Al-Suwaira general hospital and to find out the association between nurses and their socio-demographic characteristic. The study was started from March 5th, 2017 to September 31th, 2017. The sample was Non - probability (purposive) sample of (100) nurses were selected according to the study that are actual working in nursing department in Al-Suwaira General Hospital. The data were collected by direct interview using specific questionnaire thats composed of three parts (27) items which are: Part (1) Socio-demographic characteristics which included seven items (age, gender, marital status, level of education, participation in training courses or scientific conferences inside or outside Iraq and engaged in the nursing by your choice). Part (2) which deals with job satisfaction and includes (10) items and Part (3) which deals with job performance including (10) items. Data were analyzed by using (SPSS) package version 20. Descriptive data through determination of: Frequency, percentage and mean of score. Inferential statistical data analysis approach: used by enforcement of the Chi –square test used for determining the association between Socio-demographic characteristics and job satisfaction, job performance, testing the significant of the contingency coefficient. For this study the significant P-value ≤ 0.05. Results: ( (77%) were female, (56%) were married, the total grade level of job satisfaction is low, and present highly statistical significant association between items which is related to job satisfaction and gender and highly statistical significant association between the items related to the job performance and age. Recommendations: The study recommends that establish and follow up programs about job satisfaction to increase job performance